Seasonal variation and source apportionment of heavy metals in the Jhelum river: Implications for water security - Muhammad Faisal; Feng Wu; Muhammad Waseem Boota; Shan-e-hyder Soomro; Muhammad Naeem; Yuzhong Zhang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Climate driven drought risk and machine learning approaches for urban resilience and sustainable water governance - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Sher Ali; Sana Nazli; Caihong Hu; Jiali Guo (Environmental Research, 2026)

Integrating crowdsourced geospatial intelligence and urban morphology for urban waterlogging risk mapping in Karachi, Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Chengshuai Liu; Junaid Abdul Wahid; Jiali Guo; Xiaotao Shi; Gul-e-Zehra Soomro (Climatic Change, 2026)

Social media sentiment exposure to climate-induced floods and risk responses to the 2022 flood in Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Jiali Guo; Caihong Hu; Muhammad Faisal; Junaid Abdul Wahid; Gul-e-Zehra Soomro (Journal of Environmental Management, 2026)

Polystyrene microplastics at environmentally realistic concentrations exacerbate diatom blooms caused by phosphorus pollution: Rethinking coastal eutrophication - Xuan Hou; Muhammad Waseem; Muhammad Waseem Boota; Li Mu; Yuanyuan Wei; Xiangang Hu (Water Research, 2026)

Air quality management from the lens of leveraging social media data and machine learning algorithm for hazard zoning-real-time air pollution detection in urban cities under changing climate - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Gul-e-Zehra Soomro; Muhammad Faisal; Caihong Hu; Junaid Abdul Wahid; Jiali Guo (Journal of Environmental Management, 2025)

Harnessing public sentiment discourse for early drought detection and water crisis response for strategic water management and resilient policy planning - Shan-e-hyder Soomro; Muhammad Waseem Boota; Nishan-E-hyder Soomro; Gul-e-Zehra Soomro; Jiali Guo; Caihong Hu; Junaid Abdul Wahid (Science of The Total Environment, 2025)

Urban flood management from the lens of social media data using machine learning algorithms - Muhammad Waseem Boota; Shan-e-hyder Soomro; Jikun Xu; Muhammad Irshad Ahmad; Haoming Xia; Yaochen Qin; Muhammad Bilal Idrees; Naseem Ahmad; Chaode Yan; Ayesha Yousaf; Xiaoju Ning (Journal of Hydrology, 2025)

Urban cities heatwaves vulnerability and societal responses towards hazard zoning: Social media real-time based heatwave detection using deep learning - Shan-e-hyder Soomro; Muhammad Waseem Boota; Gul-e-Zehra Soomro; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Jiali Guo; Junaid Abdul Wahid (Sustainable Cities and Society, 2025)

Unveiling concentrations of trace elements in the Lower Indus River: risks to aquatic life and human health - Muhammad Waseem Boota; Shan-e-hyder Soomro; Haoming Xia; Yaochen Qin; Muhammad Bilal Idrees; Ayesha Yousaf (Frontiers in Marine Science, 2024)
Concentration of trace elements (CTEs) is a significant environmental concern worldwide. This study assessed CTE levels in the Lower Indus River (LIR) by analyzing CTEs in water, sediments, tissues of fish ( Cirrhinus mrigala ), and macrophytes using electrothermal atomic absorption spectrometry (ETAAS) and flame atomic absorption spectrometry (FAAS). The study shows that CTE range—arsenic (As, 58.7–112.1 μg/L), lead (Pb, 59.9–95.6 μg/L), cadmium (Cd, 3.8–8.1 μg/L), nickel (Ni, 40.9–63.4 μg/L), and zinc (Zn, 590.7–847.6 μg/L)—and water parameters (temperature, pH, COD, BOD, turbidity, and alkalinity) exceeded WHO (World Health Organization) acceptable limits. The CTEs (mg/kg dried basis) were analyzed in fish tissues, and As, Cd, Cr, Cu, Hg, Ni, and Zn have the following accumulation order: liver > gill > muscle. In contrast, Ag and Pb were present in higher amounts in gills than in the liver (gill > liver > muscle). Prediction of bioavailability of CTEs, with the extraction of sediment load with EDTA, revealed that As, Cd, and Zn were among the most bioavailable elements in the LIR. Health risk assessment indicated that the presence of CTEs in the fish could pose potential adverse health effects on humans. The study emphasizes significant ecological and health concerns due to fish consumption in the affected region, noting high risks of non-carcinogenic effects. These insights are essential for policymakers and stakeholders in Sindh Province to manage and reduce trace element pollution.

From lake to fisheries: Interactive effect of climate and landuse changes hit on lake fish catch? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Majid Rasta; Caihong Hu; Chengshuai Liu; Yinghai Li; Ao li; Jijun Chen; Chunyun Zhu; Sher Ali; Jiali Guo; et al. (Environmental Research, 2024)

Research on automatic identification of coal mining subsidence area based on InSAR and time series classification - Jikun Xu; Chaode Yan; Muhammad Waseem Boota; Xuanchi Chen; Ziwei Li; Wangcheng Liu; Xu Yan (Journal of Cleaner Production, 2024)

Appraisal of Urban Waterlogging and Extent Damage Situation after the Devastating Flood - Shan-e-hyder Soomro; Muhammad Waseem Boota; Xiaotao Shi; Gul-e-Zehra Soomro; Yinghai Li; Muhammad Tayyab; Caihong Hu; Chengshuai Liu; Yuanyang Wang; Junaid Abdul Wahid; Mairaj Hyder Alias Aamir Soomro; Jiali Guo; et al. (Water Resources Management, 2024)

Distribution and bioaccumulation of trace elements in two Cyprinidae fish species in the Indus river, Pakistan, including the impact of hydraulic structure on macroinvertebrates' biodiversity - Muhammad Waseem Boota; Shan-e-hyder Soomro; Haoming Xia; Yaochen Qin; Mian Adnan Kakakhel; Chaode Yan; Luo Weiran; Jikun Xu (Environmental Research, 2024)

How effective is twitter (X) social media data for urban flood management? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Gul-e-Zehra Soomro; Xiaotao Shi; Jiali Guo; Yinghai Li; Muhammad Tayyab; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Chengshuai Liu; Yuanyang Wang; et al. (Journal of Hydrology, 2024)

Correction to: Two-dimensional hydrodynamic modeling for prediction of bank erosion and bed incision in the Indus River - Muhammad Waseem Boota; Chaode Yan; Shan-e-hyder Soomro; Muhammad Awais Zafar; Ziwei Li; Jikun Xu; Ayesha Yousaf (Acta Geophysica, 2023)

Two-dimensional hydrodynamic modeling for prediction of bank erosion and bed incision in the Indus River - Muhammad Waseem Boota; Chaode Yan; Shan-e-hyder Soomro; Muhammad Awais Zafar; Ziwei Li; Jikun Xu; Ayesha Yousaf (Acta Geophysica, 2023)

River Flood Susceptibility and Basin Maturity Analyzed Using a Coupled Approach of Geo-morphometric Parameters and SWAT Model - Shan-e-hyder Soomro; Caihong Hu; Muhammad Waseem Boota; Zubair Ahmed; Liu Chengshuai; Han Zhenyue; Li Xiang; Mairaj Hyder Alias Aamir Soomro (Water Resources Management, 2022)

Mapping flood extend and its impact on land use/land cover and settlements variations: a case study of Layyah District, Punjab, Pakistan - Shan-e-hyder Soomro; Caihong Hu; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Shengqi Jian; Zeeshan Zafar; Xiaoping Li (Acta Geophysica, 2021)

Comparative study of flash flood in ungauged watershed with special emphasizing on rough set theory for handling the missing hydrological values - Muhammad Waseem Boota; Chaode Yan; Tanveer Abbas; Ziwei Li; Ming Dou; Ayesha Yousaf (Natural Hazards, 2021)